2020
DOI: 10.1007/s42399-020-00245-9
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the HPV Type Frequency in a Federal High-Specialty Hospital of Mexico City: Is HPV16 Our Main Problem?

Abstract: Human papillomavirus (HPV) is the most common sexually transmitted infection worldwide and a necessary condition for cervical cancer (CeCa) development. HPV types 16 and 18 are the most common in cervical lesions (CLs); therefore, specific vaccines have reduced cervical neoplasia. In 2015, HPV16 presented the highest frequency in CLs (~28%); however, types 31, 45, 52, and 58 were also detected, suggesting that other HPV types may have impact on healthcare. Here, we typified 30 patients with CLs from the "Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Similarly, Aziz H, et al reported in a population of Punjab, Pakistan than HPV-6 was the most frequent HPV-genotype found in 25% of infected women, however, the prevalence observed in our population was lower (13.2%) [18]. Even more, HPV-16, -58, -59, and -31 genotypes were the most common HR-genotypes in patients with cervical lesions, while, types HPV-6, 61, and 53 were the most common LR-genotypes in the same group of patients (similar to a previously published study) [19]. Contrary to the results reported by Jácome Galarza, et al [20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, Aziz H, et al reported in a population of Punjab, Pakistan than HPV-6 was the most frequent HPV-genotype found in 25% of infected women, however, the prevalence observed in our population was lower (13.2%) [18]. Even more, HPV-16, -58, -59, and -31 genotypes were the most common HR-genotypes in patients with cervical lesions, while, types HPV-6, 61, and 53 were the most common LR-genotypes in the same group of patients (similar to a previously published study) [19]. Contrary to the results reported by Jácome Galarza, et al [20].…”
Section: Discussionsupporting
confidence: 89%
“…Copy@ Thompson Bonilla María del Rocío location analysed and determinants of health associated [17,19,[23][24][25][26][27][28][29][30]. It is well established than co-infection among HPV-genotypes is common in women, and men [17].…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%